Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12885-021-08394-3
|View full text |Cite|
|
Sign up to set email alerts
|

Bridging the research to practice gap: a systematic scoping review of implementation of interventions for cancer-related fatigue management

Abstract: Background Cancer-related fatigue (CRF) is one of the most common and distressing symptoms in people with cancer. Although efficacy of interventions for CRF have been extensively investigated, less has been done to ensure successful translation into routine clinical practice. The aim of this systematic scoping review was to synthesise knowledge surrounding the implementation of CRF interventions, summarise the processes and outcomes of implementation strategies used, and identify opportunities … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Most reviews focused on cancer-related fatigue (n = 8), with the remaining reviews addressing post-viral fatigue (n = 1) and Systemic Lupus Erythematosus (SLE) (n = 1). Four reviews focused exclusively on fatigue [23][24][25][26] and six on a range of symptoms including fatigue [22,[27][28][29][30][31]. A wide range of interventions were included in the reviews, including lifestyle (e.g.…”
Section: Results Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reviews focused on cancer-related fatigue (n = 8), with the remaining reviews addressing post-viral fatigue (n = 1) and Systemic Lupus Erythematosus (SLE) (n = 1). Four reviews focused exclusively on fatigue [23][24][25][26] and six on a range of symptoms including fatigue [22,[27][28][29][30][31]. A wide range of interventions were included in the reviews, including lifestyle (e.g.…”
Section: Results Overviewmentioning
confidence: 99%
“…Only self-management summary data were extracted. Half of included reviews (n = 4) focused exclusively on self-management [22][23][24]27]. Across the primary studies, a total of 31 different outcome measures were used to measure fatigue as a primary outcome (Supplementary File 2).…”
Section: Results Overviewmentioning
confidence: 99%
“…1 2 A recent scoping review on the implementation of CRF management strategies into clinical practice identified a lack of high-quality studies in the literature which also highlights the disconnect between effective CRF interventions and routine clinical care. 23 As a key implementation strategy, the concept of a 'CRF clinic' is one successful method to facilitate the systematic assessment and management of CRF in cancer survivors. 24 25 These clinics are often physician-led, provided in well-resourced centres, and require cancer survivors to attend face-toface appointments at the cancer centre.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…For instance, 30-60% of cancer patients undergoing treatment reportedly develop severe cancer-related fatigue (CRF), which can lead to treatment interruption because of poor results from reduced physical function and reduced motor capacity [1]. Fatigue usually decreases within a year after treatment completion, but CRF is expected to last for months or even years in a small subset of patients after successful treatment [2]. In addition, cancer patients may develop serious negative emotions such as depression and anxiety, which further adversely affect the overall quality of life.…”
Section: Introductionmentioning
confidence: 99%